Peningkatan Pemahaman Siswa Kelas Dua SD N 3 Tugu Terhadap Kaidah Baca Tulis Al-Qur’an (BTQ) Melalui Media Picture Book - Fiji Lestari; Kholifatul Masitoh; Nasywa Muhimmatul Husna; Siti Fatimah; Atim Rinawati (Tarbi: Jurnal Ilmiah Mahasiswa, 2023)
This study aims to determine the increase in students' understanding of the rules of reading and writing the Qur'an through picture book media for grade 2 SD N 3 Tugu. This research is a classroom action research which was carried out in four meetings, the four meetings consisted of two stages. Each meeting consists of planning, implementation, observation, and reflection stages. The research subjects were second grade students of SD N 3 Tugu. Data collection techniques using observation, interviews, and tests. The results of the first stage of data analysis showed that as many as 65% of students got an average score in learning hijaiyah letters using picture book media. While in the second stage as many as 87% of students obtained scores above the average in recognizing hijaiyah letters using picture book media. So it can be concluded that there is an increase in knowing children's hijaiyah letters with picture book media.